LEADERSHIP DAN MANAJEMEN KURIKULUM DALAM PENDIDIKAN - Sinar; Widyawati; Al Malik Fahd; Hamdani Hamid; Ahrana; Sulkifli (As-Sulthan Journal of Education, 2025)
This paper explores the interrelation between leadership and curriculum management in the educational context. Leadership, particularly by school principals, plays a vital role in directing and managing the effective implementation of the curriculum. Meanwhile, curriculum management is a systematic process that includes planning, implementation, evaluation, and development of learning content to align with student needs and current societal demands. The success of curriculum management is strongly influenced by the leadership style and model applied. Visionary and transformational leadership has been proven to foster innovation in curriculum design and execution. Through a descriptive-qualitative approach and literature review, this paper concludes that the synergy between effective leadership and organized curriculum management is a key factor in improving educational quality in schools.